Analisis Yuridis Terhadap Sengketa Hak Cipta atas Lagu ‘SKJ88’: Studi Kasus Putusan Nomor 66 PK/Pdt.Sus-HKI/2023 - Hilda Ersella; Mariani; Boen Sidodo; Yadi Marsidi; Devina Sahara Amru; Hosea Putra Togatorop; Khairunnisa Aulia Ikramina Maulana (Policy and Law Journal, 2025)
This study uses the Supreme Court Decision No. 66 PK/Pdt.Sus-HKI/2023 as a case study to examine copyright protection in the “Physical Fitness Gymnastics 88” music dispute. In this study, the case study and legislative methods are combined with a normative legal strategy. The primary objective of this study is to examine the application of legal protection against copyright infringement in the digital age and its impact on the development of intellectual property rights (IPR) legislation in Indonesia. The study's findings indicate that the Supreme Court's decision provides tangible protection for creators by imposing significant financial penalties and immaterial damages on infringers. This decision supports more progressive legal protection in the face of digital era challenges and underscores the serious and unforgivable nature of copyright infringement. In addition to raising public legal awareness and setting an important precedent in the enforcement of intellectual property rights (IPR) laws, the implications of this decision encourage collaboration between the government, users, and artists to build a stronger and fairer ecosystem for copyright protection.